Thymoquinone and its pharmacological perspective: A review - Shabana Tabassum; Norhayati Rosli; Solachuddin Jauhari Arief Ichwan; Puranjan Mishra (Elsevier, 2021)
Thymoquinone (TQ) a plant-derived dietary of Nigella sativa, is a well-known traditionally and clinically used natural medicine. The diverse pharmacological properties of TQ have been identified including antimicrobial, antihistamine, antioxidant effects, immunomodulator, and anticancer activities. In this review, investigations regarding the effects of TQ in oxidative stress, immunomodulation, and various type of cancer have been reviewed based on the available relevant literature. TQ-based induction of the immune system by modulating different inflammatory mediators i.e., cytokines, leukins, interleukins, interferons, and other immune cells have been reviewed here. Several studies signified remarkable anticancer potentials of TQ depending upon its concentration and type of cancer cell. Conclusively, understanding pharmacological activities of TQ its molecular mechanism could help researchers to develop a potent analog of well-established chemotherapeutic drugs in clinical trials.